The Influence of Work Ethic and Organizational Culture on Employee Performance at the Regional Financial Management Agency of West Pasaman Regency - Harum, Beny; Susanti, Febsri (Bina Bangsa International Journal of Business and Management, 2023)
This study aims to determine the effect of competence, individual characteristics and lacus of control partially and simultaneously on the performance of employees at the secretariat of DPRD Pariaman City. Samples were selected using the total sampling method. The sample in this study were employees of the DPRD Pariaman City Secretariat, totaling 40 people. The data collection technique used a questionnaire, while the data analysis method used validity and reliability tests, classical assumptions, multiple linear regression analysis and statistical tests (t test, F test and coefficient of determination). The results showed that the competence variable had an effect on employee performance at the DPRD secretariat of Pariaman City, with a value of tcount 3.739 > ttable 2.021 at a significant level of 0.001 <0.05.  This study aims to determine the effect of work ethic and organizational culture partially and simultaneously on employee performance at the Regional Financial Management Agency (BPKD) of West Pasaman Regency. The sample was selected using the total sampling method. The sample in this study were employees of the Regional Financial Management Agency (BPKD) of West Pasaman Regency, totaling 70 people. The data collection technique used a questionnaire, while the data analysis method used validity and reliability tests, classical assumptions, multiple linear regression analysis and statistical tests (t test, F test and coefficient of determination).               The results showed that the variables of work ethic and organizational culture had an effect on employee performance at the Regional Financial Management Agency (BPKD) of West Pasaman Regency, with a regression coefficient of -0.386 and a significant value of 0.000 (< 0.05). Then Organizational Culture has a positive and significant effect on Employee Performance at the Regional Financial Management Agency (BPKD) of West Pasaman Regency with a regression coefficient value of 1.119 and a significant value of 0.000 (<0.05). The coefficient of determination of 0.763 or 76.3% is influenced by the work ethic and organizational culture, while the remaining 23.7% is influenced by other factors not examined in this study